Democracy, Market Liberalization, and Political Preferences - Grosjean, Pauline; Senik, Claudia (The Review of Economics and Statistics, 2011)
We estimate the impact of market development and democratization on subjective political preferences. We rely on the specific situation of frontier zones and the considerable regional variations in culture and economic development in the countries of the former socialist bloc for identification. Using a survey conducted in 2006, we find a positive and significant effect of democracy on support for a market economy, but no effect of market liberalization on support for democracy. Hence, in contrast with the conventional wisdom concerning the sequencing of political and economic reforms, democratization may become a necessary condition to obtain public support for further economic liberalization.